Cost-effectiveness of fibronectin testing in a triage in women with threatened preterm labor: alleviation of pregnancy outcome by suspending tocolysis in early labor (APOSTEL-I trial) - Scherjon Sicco A; Lotgering Fred K; van Pampus Maria G; Opmeer Brent C; Kwee Anneke; van Eyck Jim; Duvekot Johannes J; Derks Jan B; Cornette Jérôme; Bolte Annemiek C; Bloemenkamp Kitty WM; Scheepers Hubertina CJ; et al. (BMC, 2009)
Abstract Background At present, women with threatened preterm labor before 32 weeks of gestation are, after transfer to a perinatal center, treated with tocolytics and corticosteroids. Many of these women are treated unnecessarily. Fibronectin is an accurate predictor for the occurrence of preterm birth among women with threatened preterm labor. We will assess whether triage of these women with fibronectin testing, cervical length or their combination is cost-effective. Methods/Design We will investigate a prospective cohort of women referred to a perinatal centre for spontaneous threatened preterm labor between 24 and 34 weeks with intact membranes. All women will be tested for fibronectin and cervical length. Women with a cervical length <10 mm and women with a cervical length between 10-30 mm in combination with a positive fibronectin test will be treated with tocolytics according to local protocol. Women with a cervical length between 10-30 mm in combination with a negative fibronectin test will be randomised between treatment with nifedipine (intervention) and placebo (control) for 48 hours. Women with a cervical length > 30 mm will be managed according to local protocol. Corticosteroids may be given to all women at the discretion of the attending physician. Primary outcome measure will be delivery within 7 days. Secondary outcome measures will be neonatal morbidity and mortality, complications of tocolytics, costs and health related quality of life. The analysis will be according to the intention to treat principle. We anticipate the probability on preterm birth within 7 days in the group of women with a negative fibronectine test to be 5%. Two groups of 110 women will be needed to assure that in case of non-inferiority the difference in the proportion of preterm deliveries < 7 days will be within a prespecified boundary of 7.5% (one sided test, β 0.2, α 0.05). Data obtained from women with a positive and negative fibronectin tests in both the cohort study and the trial will be integrated in a cost-effectiveness analysis that will assess economic consequences of the use of fibronectin. Discussion This study will provide evidence for the use of fibronectin testing as safe and cost-effective method in a triage for threatened preterm labor. Trial registration Nederlands Trial Register (NTR) number 1857, http://www.trialregister.nl.